Insights into the mechanism of carbon dioxide and propylene oxide ring-opening copolymerization using a Co(III)/K(I) heterodinuclear catalyst - Deacy, AC; Phanopoulos, A; Lindeboom, W; Buchard, A; Williams, CK (American Chemical Society, 2022)
A combined computational and experimental investigation into the catalytic cycle of carbon dioxide and propylene oxide ring-opening copolymerization is presented using a Co(III)K(I) heterodinuclear complex (Deacy, A. C. Co(III)/Alkali-Metal(I) Heterodinuclear Catalysts for the Ring-Opening Copolymerization of CO2 and Propylene Oxide. J. Am. Chem. Soc. 2020, 142(45), 19150−19160). The complex is a rare example of a dinuclear catalyst, which is active for the copolymerization of CO2 and propylene oxide, a large-scale commercial product. Understanding the mechanisms for both product and byproduct formation is essential for rational catalyst improvements, but there are very few other mechanistic studies using these monomers. The investigation suggests that cobalt serves both to activate propylene oxide and to stabilize the catalytic intermediates, while potassium provides a transient carbonate nucleophile that ring-opens the activated propylene oxide. Density functional theory (DFT) calculations indicate that reverse roles for the metals have inaccessibly high energy barriers and are unlikely to occur under experimental conditions. The rate-determining step is calculated as the ring opening of the propylene oxide (ΔGcalc† = +22.2 kcal mol–1); consistent with experimental measurements (ΔGexp† = +22.1 kcal mol–1, 50 °C). The calculated barrier to the selectivity limiting step, i.e., backbiting from the alkoxide intermediate to form propylene carbonate (ΔGcalc† = +21.4 kcal mol–1), is competitive with the barrier to epoxide ring opening (ΔGcalc† = +22.2 kcal mol–1) implicating an equilibrium between alkoxide and carbonate intermediates. This idea is tested experimentally and is controlled by carbon dioxide pressure or temperature to moderate selectivity. The catalytic mechanism, supported by theoretical and experimental investigations, should help to guide future catalyst design and optimization.